BLENDING WAS NOT AN OPTION: VARIATION THEORY AND RELUCTANT INTERNATIONAL DISTANCE LEARNERS - Starr-Glass, David (South African Journal of Higher Education, 2016)
This short paper reflects on experiences gained in designing what was intended to be a blended course. In the event, a blended option was not possible and the paper explores how variation theory was then used to transition international learners, skeptical about distant learning, from in-person to distant learning modalities. The role of variation, in approaching both the content and process of the learning experience, was presented during the two in-person lectures at the outset of the course. While results are preliminary and tentative, the use of variation seems to have positively impacted learner understanding of subject matter and the online learning experience.